Analisis Infrensial Tingkat Pengetahuan dengan Tindakan Pengelolaan Sampah (Medis dan Non Medis) Rumah Tangga Selama Pandemi Covid-19 di DKI Jakarta - Khairillah Fathinnuzul Heryawan; Jojok Mukono (Universitas Airlangga, 2023)
Background: In the span of 2019-2021, the source of waste is always dominated by household waste, from the total composition of waste based on its source. The coronavirus disease 2019 (COVID-19) pandemic has caused an increase in medical waste sourced from household waste. This increase is at risk of transmitting COVID-19 to many people if it is not managed properly. Objectives: This study aims to determine the relationship between the level of knowledge and waste management actions by reducing, reusing, recycling, segregating waste by its types, and segregating medical and non-medical waste at household scale during the COVID-19 pandemic in the Special Capital Region of Indonesia. DKI Jakarta. Methods: This research method used inferential analysis and a cross-sectional design study. The respondents of this study were 226 people who live in DKI Jakarta with an age range of 18-60 years. The independent variable of this study was the knowledge of the people of DKI Jakarta regarding waste. Dependent variables include the application of reducing, reusing, recycling, segregating waste by its types, and segregating medical and non-medical waste. Results: The results showed a significant value between the independent and dependent variables. The significance value was between knowledge and the application of 3R (p=0.395), between knowledge and segregating waste by its types (p=0.167), and between knowledge and segregating medical and non-medical waste (p=0.031). Conclusions: There was no significant relationship between the knowledge variable and the application of 3R because the significance value is p>0.05. Likewise, the knowledge variable and the sorting of organic and non-organic waste. However, there is a relationship between knowledge and sorting medical and non-medical waste with a p-value of 0.031 (p<0.05).